2020
DOI: 10.3892/etm.2020.8762
|View full text |Cite
|
Sign up to set email alerts
|

Role of pulmonary function and FeNO detection in early screening of patients with ACO

Abstract: Measurement of fractional exhaled nitric oxide (FeNO) is a quantitative and non-invasive approach to examine airway inflammation, which is a powerful aid in diagnosing chronic disorders of airways like asthma. Diagnostic value of FeNO and relevant indices on pulmonary function in the patients with asthma and chronic obstructive pulmonary disease (COPD) was evaluated. A total of 164 patients [58 asthma, 49 COPD and 57 asthma-COPD overlap (ACO)] were randomly recruited. FeNO, pulmonary ventilation function, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The FEV1/FVC ratio, an important parameter of airflow obstruction, 25 was found to be significantly lower in patients with T2-CRSwNP(h) than in non-T2-CRSwNP(h) patients, and FeNO was negatively correlated with the FEV1/FVC ratio in patients with CRSwNP. The results of this study suggest that FeNO can serve as an effective marker for assessing airway obstruction in patients with CRSwNP.…”
Section: Discussionmentioning
confidence: 99%
“…The FEV1/FVC ratio, an important parameter of airflow obstruction, 25 was found to be significantly lower in patients with T2-CRSwNP(h) than in non-T2-CRSwNP(h) patients, and FeNO was negatively correlated with the FEV1/FVC ratio in patients with CRSwNP. The results of this study suggest that FeNO can serve as an effective marker for assessing airway obstruction in patients with CRSwNP.…”
Section: Discussionmentioning
confidence: 99%
“…An increased neutrophil count in the sputum of ACO patients who were mostly ex-smokers was suggested to be a promising ACO-specific marker [43]. However, their sputum eosinophil level was equivalent to that in asthma patients [44], and thus FeNO may not be a helpful indicator for distinguishing ACO and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear which one is more suitable in diagnosing ACO. Although the positive BDT result alone is limited in differentiating between asthma, COPD, and ACO, COPD has a lower ΔFEV 1 (in mL) than asthma and ACO, and bronchodilator response (BDR) was helpful in the early screening of ACO [ 25 ]. Besides, BDR was vital in identifying different phenotypes of ACO [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The two aforementioned studies showed a low sensitivity, indicating that FeNO alone is useful but difficult to use for differentiating between ACO and COPD. Recently, Wang reported that ΔFEV 1 and FeNO were significantly different in ACO compared with COPD alone, which indicated that BDR combined with FeNO may be helpful in the early screening of ACO [ 25 ]. However, there is still a lack of an optimal value of ΔFEV 1 for differentiating between asthma, COPD, and ACO in patients with a positive BDT result.…”
Section: Introductionmentioning
confidence: 99%